Feasibility of plant-expression system for production of recombinant anti-human IgE: An alternative production platform for therapeutic monoclonal antibodies - Hanittinan, Oranicha; Rattanapisit, Kaewta; Malla, Ashwini; Tharakhet, Kittipan; Ketloy, Chutitorn; Prompetchara, Eakachai; Phoolcharoen, Waranyoo (Frontiers in Plant Science, 2022)
Omalizumab, the anti-immunoglobulin IgE antibody is the only approved and available monoclonal antibody as an auxiliary medicament for the severe respiratory allergic reactions. It forms small size immune complexes by binding to free IgE, thereby inhibiting the interaction of IgE with its receptors. Additionally, the anti-IgE can also differently shape the airflow by impeding the stimulation of IgE receptors present on structural cells in the respiratory tract. The present study aimed to use plants as an expression system for anti-human IgE antibody production, using Nicotiana benthamiana as hosts. Recombinant Agrobacterium tumefaciens containing heavy chain (HC) and light chain (LC) domains of anti-human IgE were co-transformed in N. benthamiana. The assembling of the antibody and its expression was detected by SDS-PAGE and Western blot analysis. The functional ability of the anti-IgE antibody was determined via its binding capacity with target IgE by ELISA and the inhibition of basophil activation. The anti-human IgE mAb generated in plants was shown to be effective in binding to its target IgE and inhibit the IgE-crosslink in RS-ATL8 reporter cells. Although, antibody yield and purification process have to be further optimized, this study demonstrates the use of plant expression system as a promising platform for the production of Omalizumab which showed a comparable in vitro function to that of commercial Omalizumab (Xolair) in the inhibition of basophil activation.